A novel glycerol hydrogenation catalyst and a preparation method thereof
By preparing a one-dimensional conjugated coordination polymer material and a quartz sand composite catalyst, the problems of low selectivity and insufficient stability of existing catalysts were solved, achieving efficient conversion of glycerol and selectivity of 1,2-propanediol, which has good environmental and economic value.
Patent Information
- Application Number
- CN202410189628.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-20
- Publication Date
- 2026-08-25
- Estimated Expiration
- 2044-02-20
Smart Images

Figure CN118106034B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of chemical technology, specifically a novel glycerol hydrogenation catalyst and its preparation method. Background Technology
[0002] With population growth and rapid social production development, human society's energy consumption has been increasing year by year. Currently widely used non-renewable fossil fuels such as coal, oil, and natural gas are becoming increasingly depleted, and their prices are soaring, greatly increasing the demand for renewable energy development. Among these, bioenergy has received significant research attention, and in recent years, biodiesel production has increased rapidly. As a byproduct of biodiesel production, the production of glycerol has also surged. However, due to the high cost of purifying crude glycerol, a large amount of excess crude glycerol has not been effectively utilized, resulting in substantial waste and hindering the development of biodiesel.
[0003] Catalytic hydrogenation of crude glycerol can produce a variety of high-value-added C3 products, including acrolein, acrylic acid, propylene glycol, and glyceric acid. Among these, 1,2-propanediol has wide applications in pharmaceuticals, cosmetics, plastics, and coatings. However, traditional 1,2-propanediol production primarily relies on petroleum, leading to unsustainable processes and high energy consumption, resulting in expensive production costs. Therefore, hydrogenating crude glycerol to produce 1,2-propanediol solves the problems of glycerol waste and pollution while yielding a high-value-added product, offering both environmental and economic benefits.
[0004] Currently, the hydrogenation reduction of glycerol to 1,2-propanediol has become a mature industrial reaction. Commonly used catalysts include copper, silver, and nickel. In addition, some novel catalysts, such as noble metal nanoparticles, have been studied and applied to this reaction to improve reaction efficiency and selectivity. However, problems such as low selectivity, insufficient catalyst lifetime, and environmental pollution still exist. Therefore, improving the selectivity of the 1,2-propanediol product, extending catalyst lifetime, and exploring more environmentally friendly catalyst materials are of great significance and value.
[0005] One-dimensional conjugated coordination polymers are a class of organic-inorganic hybrid materials based on coordination bonds. They possess a linearly arranged porous structure, typically formed by organic ligands and metal ions or clusters linked by coordination bonds, exhibiting highly controllable structures and assembly methods. By selecting different organic ligands and metal ions or clusters, structural parameters such as the material's combination, length, and pore size distribution can be adjusted, thereby achieving precise control over the material's properties. Furthermore, one-dimensional coordination polymers possess abundant functional groups, allowing for surface modification and functionalization. Introducing new functional groups or altering the structure of ligands can endow the materials with more chemical reaction sites, thus expanding their application areas. The high density of strongly polar coordination bonds in the materials endows them with excellent thermal and chemical stability. They can maintain their structural integrity and functional properties over a wide range of temperature and environmental conditions, exhibiting long lifespans and good cycling stability.
[0006] In practice, existing glycerol hydrogenation catalysts for the preparation of 1,2-propanediol exhibit low selectivity and insufficient catalyst stability, leading to environmental pollution. Therefore, a novel glycerol hydrogenation catalyst and its preparation method are proposed to address these issues. Summary of the Invention
[0007] In order to overcome the shortcomings of the prior art, at least one technical problem raised in the background art is solved.
[0008] The technical solution adopted by this invention to solve its technical problem is: a method for preparing a novel glycerol hydrogenation catalyst according to this invention, comprising the following steps: S1. Dissolve phenyltetramine tetrahydrochloride in deionized water and stir to obtain a homogeneous solution; S2. Dissolve the metal salt in deionized water and add it dropwise to the homogeneous solution obtained in S1; S3. Slowly add ammonia water to the S2 solution to adjust the pH to about 8. Stir the reaction at room temperature. A dark precipitate will gradually form in the solution. S4. After the reaction is complete, the resulting mixture is filtered and the filter residue is washed several times with acetone, water and ethanol respectively. After drying, a one-dimensional conjugated coordination polymer material is obtained, denoted as M-GHP. S5. The M-GHP material obtained in S4 is pressed into tablets, ground and granulated, and then thoroughly mixed with quartz sand to obtain a quartz sand-supported M-GHP composite catalyst, denoted as M-GHP@SiO2. S6. The M-GHP@SiO2 composite catalyst material obtained in S5 is loaded into the reaction tube and carried out the catalytic hydrogenation reaction of glycerol in a fixed bed reactor. S7. The obtained product is qualitatively and quantitatively detected by gas chromatography.
[0009] Benzenetetramine tetrahydrochloride was dissolved in water, and a metal salt solution was added. Ammonia was slowly added dropwise to adjust the pH to 8, gradually consuming protons and activating the coordination ability of the amine functional groups. This activated the amine groups to undergo coordination polymerization with metal ions, generating a one-dimensional conjugated coordination polymer, which gradually precipitated from the solution. After the reaction, the solid product was obtained by filtration. Impurities were washed away with water, acetone, and ethanol, and the product was dried to obtain the one-dimensional conjugated coordination polymer material. The prepared one-dimensional conjugated coordination polymer material was granulated, mixed with quartz sand, and packed into the reaction tube of a fixed-bed reactor. The hydrogenation reduction of glycerol to 1,2-propanediol was catalytically carried out under high temperature and high pressure conditions.
[0010] Preferably, the molar ratio of phenyltetramine tetrahydrochloride and metal salt in S1 and S2 is 1:1.1.
[0011] Preferably, the metal salt in S2 includes, but is not limited to, FeCl3, CoCl2·6H2O, CuSO4·5H2O, NiCl2·6H2O, and zinc acetate.
[0012] Preferably, in S1 and S2, the amounts of phenyltetramine tetrahydrochloride and metal salt are 1 mmol and 1.1 mmol, respectively, and the amounts of deionized water are 40 mL and 30 mL, respectively.
[0013] Preferably, the stirring reaction time at room temperature in step S3 is 6 hours.
[0014] Preferably, in step S5, 20-80 mesh particles are selected after M-GHP granulation, and the quartz sand particles used are 20-80 mesh.
[0015] Preferably, the loading amount of the M-GHP@SiO2 composite catalyst in S6 is 10 g, and the flow rates of hydrogen and nitrogen during the catalytic reaction are both 50 mL·min. -1 The reaction temperature is 210-240°C, the reaction pressure is 1.8-2 MPa, and the glycerol mass fraction is 50%.
[0016] Preferably, ethanol is added as an internal standard to the sample to be tested in S7. The quantitative analysis of the hydrogenolysis products in S7 is performed using a gas chromatograph from Zhongjiao Jinyuan, model GC-7820. The chromatographic column used is SE-54 (crosslinked), with dimensions of (50 m × 0.32 mm × 0.5 µm). An FID detector is used, with detector temperature at 290 °C, injection port temperature at 290 °C, column temperature at 220 °C, valve box temperature at 100 °C, and converter temperature at 360 °C. The column inlet pressure is 0.3 MPa, the injection method is manual, and the injection volume is 0.5 μL. The carrier gas tail gas is H2: 30 mL / min, Air: 300 mL / min, N2: 25 mL / min. The amount of glycerol hydrogenolysis products is determined according to the internal standard method, with ethanol selected as the internal standard, and a standard curve of glycerol and 1,2-propanediol is determined.
[0017] A novel glycerol hydrogenation catalyst, characterized in that: the glycerol hydrogenation catalyst is prepared by the above-mentioned method for preparing a novel glycerol hydrogenation catalyst; the Ni-GHP and Zn-GHP have strong crystallinity, the Cu-GHP has weak crystallinity, the Fe-GHP and Co-GHP are amorphous, the Ni-GHP, Cu-GHP and Zn-GHP are rod-shaped aggregates, and the Fe-GHP and Co-GHP are amorphous clusters.
[0018] The beneficial effects of this invention are: 1. This invention provides a novel glycerol hydrogenation catalyst and its preparation method. The invention uses a type of one-dimensional conjugated coordination polymer material as the glycerol hydrogenation catalyst. By changing the type of metal ions, excellent glycerol hydrogenation reduction performance is obtained, achieving a glycerol conversion rate of 99.99% and a 1,2-propanediol selectivity of 97.10% under conditions of 210 °C and 2.0 MPa. The one-dimensional conjugated coordination polymer material of this invention has a simple preparation process, excellent catalytic performance, good long-term stability, and commercialization prospects.
[0019] 2. This invention provides a novel glycerol hydrogenation catalyst and its preparation method. The Ni-GHP@SiO2 composite catalyst catalyzes the hydrogenation reduction of glycerol in a fixed-bed reactor and can operate continuously for 1000 hours. The reaction is stable and there is no catalyst deactivation. Compared with the prior art, the catalyst prepared by this invention can achieve higher catalytic activity, longer service life, and greater selectivity for 1,2-propanediol under lower pressure and temperature conditions. Attached Figure Description
[0020] The accompanying drawings, which are included to provide a further understanding of the invention and form part of this application, illustrate exemplary embodiments of the invention and, together with their description, serve to explain the invention and do not constitute an undue limitation thereof. In the drawings: Figure 1 This is a flowchart of the method of the present invention; Figure 2 Microstructure images of one-dimensional conjugated coordination polymer materials (a) Fe-GHP, (b) Co-GHP, (c) Ni-GHP, (d) Cu-GHP, and (e) Zn-GHP. Figure 3 The infrared spectrum of a phenylenetetramine-one-dimensional coordination polymer material is shown. Figure 4 X-ray diffraction pattern of a one-dimensional conjugated coordination polymer material; Figure 5 TEM images and elemental distribution maps of Ni-GHP materials; Figure 6 Gas chromatogram of a mixture of ethanol, 1,2-propanediol, and glycerol; Figure 7 For 1,2-propanediol:ethanol and glycerol:ethanol gas chromatographic peak area ratio versus molar ratio standard curve; Figure 8 This is a schematic diagram of the reaction process conditions and results. Detailed Implementation
[0021] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0022] Example 1 Please see Figure 1-8 As shown, a method for preparing a novel glycerol hydrogenation catalyst includes the following steps: S1. Dissolve phenyltetramine tetrahydrochloride in deionized water and stir to obtain a homogeneous solution; S2. Dissolve the metal salt in deionized water and add it dropwise to the homogeneous solution obtained in S1; S3. Slowly add ammonia water to the S2 solution to adjust the pH to about 8. Stir the reaction at room temperature. A dark precipitate will gradually form in the solution. S4. After the reaction is complete, the resulting mixture is filtered and the filter residue is washed several times with acetone, water and ethanol respectively. After drying, a one-dimensional conjugated coordination polymer material is obtained, denoted as M-GHP. S5. The M-GHP material obtained in S4 is pressed into tablets, ground and granulated, and then thoroughly mixed with quartz sand to obtain a quartz sand-supported M-GHP composite catalyst, denoted as M-GHP@SiO2. S6. The M-GHP@SiO2 composite catalyst material obtained in S5 is loaded into the reaction tube and carried out the catalytic hydrogenation reaction of glycerol in a fixed bed reactor. S7. The obtained product is qualitatively and quantitatively detected by gas chromatography.
[0023] Benzenetetramine tetrahydrochloride was dissolved in water, and a metal salt solution was added. Ammonia was slowly added dropwise to adjust the pH to 8, gradually consuming protons and activating the coordination ability of the amine functional groups. This activated the amine groups to undergo coordination polymerization with metal ions, generating a one-dimensional conjugated coordination polymer, which gradually precipitated from the solution. After the reaction, the solid product was obtained by filtration. Impurities were washed away with water, acetone, and ethanol, and the product was dried to obtain the one-dimensional conjugated coordination polymer material. The prepared one-dimensional conjugated coordination polymer material was granulated, mixed with quartz sand, and packed into the reaction tube of a fixed-bed reactor. The hydrogenation reduction of glycerol to 1,2-propanediol was catalytically carried out under high temperature and high pressure conditions.
[0024] Please see Figure 1-8 As shown, the molar ratio of phenyltetramine tetrahydrochloride and metal salt in S1 and S2 is 1:1.1.
[0025] Please see Figure 1-8 As shown, the metal salts in S2 include, but are not limited to, FeCl3, CoCl2·6H2O, CuSO4·5H2O, NiCl2·6H2O, and zinc acetate.
[0026] Please see Figure 1-8 As shown, the amounts of phenyltetramine tetrahydrochloride and metal salt used in S1 and S2 are 1 mmol and 1.1 mmol, respectively, and the amounts of deionized water used are 40 mL and 30 mL, respectively.
[0027] Please see Figure 1-8 As shown, the stirring reaction time of S3 at room temperature is 6 h.
[0028] Please see Figure 1-8 As shown, in S5, after M-GHP granulation, 20-80 mesh particles are selected, and the quartz sand particles used are 20-80 mesh.
[0029] Please see Figure 1-8 As shown, the loading amount of the M-GHP@SiO2 composite catalyst in S6 is 10 g, and the flow rates of hydrogen and nitrogen during the catalytic reaction are both 50 mL·min. -1 The reaction temperature is 210-240°C, the reaction pressure is 1.8-2 MPa, and the glycerol mass fraction is 50%.
[0030] Please see Figure 1-8 As shown, ethanol was added as an internal standard to the sample in S7. The quantitative analysis of the hydrogenolysis products in S7 was performed using a gas chromatograph (GC-7820) from Zhongjiao Jinyuan. The column used was SE-54 (crosslinked), with dimensions of 50 m × 0.32 mm × 0.5 µm. An FID detector was used, with detector temperature at 290 °C, injection port temperature at 290 °C, column temperature at 220 °C, valve box temperature at 100 °C, and converter temperature at 360 °C. The column inlet pressure was 0.3 MPa, and the injection method was manual, with an injection volume of 0.5 μL. The carrier gas tail gas was H2: 30 mL / min, Air: 300 mL / min, and N2: 25 mL / min. The amount of glycerol hydrogenolysis products was determined using the internal standard method, with ethanol selected as the internal standard, and a standard curve of glycerol and 1,2-propanediol was measured.
[0031] Please see Figure 1-8 As shown, a novel glycerol hydrogenation catalyst is prepared by the above-described method for preparing a novel glycerol hydrogenation catalyst. The Ni-GHP and Zn-GHP exhibit strong crystallinity, while Cu-GHP exhibits weak crystallinity. Fe-GHP and Co-GHP are amorphous. Ni-GHP, Cu-GHP, and Zn-GHP are rod-shaped aggregates, while Fe-GHP and Co-GHP are amorphous clusters.
[0032] 174.63 mg (1 mmol) of phenyltetramine tetrahydrochloride was dissolved in 40 mL of deionized water, and 178.42 mg (1.1 mmol) of ferric chloride was dissolved in 30 mL of deionized water. The ferric chloride solution was added dropwise to the phenyltetramine solution, and then ammonia was slowly added dropwise to the mixed solution to adjust the pH to about 8. After stirring at room temperature for 6 h, the precipitate was separated by filtration and washed several times with acetone, deionized water and ethanol, respectively. After drying, a one-dimensional coordination polymer material was obtained, denoted as Fe-GHP.
[0033] Fe-GHP was compressed into tablets and then ground into granules in a mortar. Catalyst particles of different sizes were separated using 20, 40, 60, and 80 mesh sieves, respectively, to obtain catalysts with sizes of 20-40 mesh, 40-60 mesh, and 60-80 mesh, denoted as Fe-GHP-2040, Fe-GHP-4060, and Fe-GHP-6080.
[0034] The catalysts of different mesh sizes were thoroughly mixed with equal masses of corresponding mesh sizes of quartz sand to obtain composite catalyst materials, which were respectively denoted as Fe-GHP@SiO2-2040, Fe-GHP@SiO2-4060 and Fe-GHP@SiO2-6080.
[0035] 10 g of the above-mentioned composite catalyst was charged into a gas-solid phase catalytic reactor. The reactor temperature was controlled at 220 °C and the pressure at 2.0 MPa. 50% crude glycerol was introduced into a mixing tank and mixed with hydrogen via heating and nitrogen purging. The hydrogen flow rate was 50 mL·min⁻¹, the nitrogen flow rate was 50 mL·min⁻¹, and the mass hourly space velocity (WHSV) of glycerol was 1.92 h⁻¹. The product was sampled, and ethanol was added as an internal standard. Qualitative and quantitative analysis of the composition was performed using gas chromatography, and the glycerol conversion and selectivity for 1,2-ethylene glycol were calculated. The catalytic activity of the catalyst was evaluated by varying the reaction temperature and pressure. The reaction process conditions and results are shown in [reference needed]. Figure 8 .
[0036] Example 2 174.63 mg (1 mmol) of phenyltetramine tetrahydrochloride was dissolved in 40 mL of deionized water, and 261.72 mg (1.1 mmol) of cobalt dichloride hexahydrate was dissolved in 30 mL of deionized water. The cobalt dichloride solution was added dropwise to the phenyltetramine solution, and then ammonia was slowly added dropwise to the mixed solution to adjust the pH to about 8. After stirring at room temperature for 6 h, the precipitate was separated by filtration and washed several times with acetone, deionized water and ethanol, respectively. After drying, a one-dimensional coordination polymer material was obtained, denoted as Co-GHP.
[0037] Co-GHP was compressed into tablets and then ground into granules in a mortar. Catalyst particles of different sizes were separated using 20, 40, 60, and 80 mesh sieves, respectively, to obtain catalysts with sizes of 20-40 mesh, 40-60 mesh, and 60-80 mesh, which were designated as Co-GHP-2040, Co-GHP-4060, and Co-GHP-6080, respectively.
[0038] The catalysts of different mesh sizes were thoroughly mixed with equal masses of corresponding mesh sizes of quartz sand to obtain composite catalyst materials, which were designated as Co-GHP@SiO2-2040, Co-GHP@SiO2-4060 and Co-GHP@SiO2-6080, respectively.
[0039] The catalytic process is the same as in Example 1; the reaction conditions and results are as follows: Figure 8 .
[0040] The catalyst can operate stably in a fixed-bed reactor for more than 200 hours without significant deactivation. Example 3 174.63 mg (1 mmol) of phenyltetramine tetrahydrochloride was dissolved in 40 mL of deionized water, and 274.65 mg (1.1 mmol) of copper sulfate pentahydrate was dissolved in 30 mL of deionized water. The copper sulfate solution was added dropwise to the phenyltetramine solution, and then ammonia was slowly added dropwise to the mixed solution to adjust the pH to about 8. After stirring at room temperature for 6 h, the precipitate was separated by filtration and washed several times with acetone, deionized water and ethanol, respectively. After drying, a one-dimensional coordination polymer material was obtained, denoted as Cu-GHP.
[0041] Cu-GHP was compressed into tablets and then ground into granules in a mortar. Catalyst particles of different sizes were separated using 20, 40, 60, and 80 mesh sieves, respectively, to obtain catalysts with sizes of 20-40 mesh, 40-60 mesh, and 60-80 mesh, denoted as Cu-GHP-2040, Cu-GHP-4060, and Cu-GHP-6080.
[0042] The catalysts of different mesh sizes were thoroughly mixed with equal masses of corresponding mesh sizes of quartz sand to obtain composite catalyst materials, which were denoted as Cu-GHP@SiO2-2040, Cu-GHP@SiO2-4060 and Cu-GHP@SiO2-6080, respectively.
[0043] The catalytic process is the same as in Example 1; the reaction conditions and results are as follows: Figure 8 .
[0044] The catalyst can operate stably in a fixed-bed reactor for more than 200 hours without significant deactivation.
[0045] Example 4 174.63 mg (1 mmol) of phenyltetramine tetrahydrochloride was dissolved in 40 mL of deionized water, and 261.46 mg (1.1 mmol) of nickel chloride hexahydrate was dissolved in 30 mL of deionized water. The nickel chloride solution was added dropwise to the phenyltetramine solution, and then ammonia was slowly added dropwise to the mixed solution to adjust the pH to about 8. After stirring at room temperature for 6 h, the precipitate was separated by filtration and washed several times with acetone, deionized water and ethanol, respectively. After drying, a one-dimensional coordination polymer material was obtained, denoted as Ni-GHP.
[0046] Ni-GHP was compressed into tablets and then ground into granules in a mortar. Catalyst particles of different sizes were separated using 20, 40, 60, and 80 mesh sieves, respectively, to obtain catalysts with sizes of 20-40 mesh, 40-60 mesh, and 60-80 mesh, denoted as Ni-GHP-2040, Ni-GHP-4060, and Ni-GHP-6080.
[0047] The catalysts of different mesh sizes were thoroughly mixed with equal masses of corresponding mesh sizes of quartz sand to obtain composite catalyst materials, which were denoted as Ni-GHP@SiO2-2040, Ni-GHP@SiO2-4060 and Ni-GHP@SiO2-6080, respectively.
[0048] The catalytic process is the same as in Example 1; the reaction conditions and results are as follows: Figure 8 .
[0049] Example 5 174.63 mg (1 mmol) of phenyltetramine tetrahydrochloride was dissolved in 40 mL of deionized water, and 201.83 mg (1.1 mmol) of zinc acetate was dissolved in 30 mL of deionized water. The zinc acetate solution was added dropwise to the phenyltetramine solution, and then ammonia was slowly added dropwise to the mixed solution to adjust the pH to about 8. After stirring at room temperature for 6 h, the precipitate was separated by filtration and washed several times with acetone, deionized water and ethanol, respectively. After drying, a one-dimensional coordination polymer material was obtained, denoted as Zn-GHP.
[0050] Zn-GHP was compressed into tablets and then ground into granules in a mortar. Catalyst particles of different sizes were separated using 20, 40, 60, and 80 mesh sieves, respectively, to obtain catalysts with sizes of 20-40 mesh, 40-60 mesh, and 60-80 mesh, which were designated as Zn-GHP-2040, Zn-GHP-4060, and Zn-GHP-6080.
[0051] The catalysts of different mesh sizes were thoroughly mixed with equal masses of corresponding mesh sizes of quartz sand to obtain composite catalyst materials, which were designated as Zn-GHP@SiO2-2040, Zn-GHP@SiO2-4060 and Zn-GHP@SiO2-6080, respectively.
[0052] The catalytic process is the same as in Example 1; the reaction conditions and results are as follows: Figure 8 .
[0053] The catalyst can operate stably in a fixed-bed reactor for more than 200 hours without significant deactivation. The catalyst can operate stably in a fixed-bed reactor for more than 1,000 hours without significant deactivation.
[0054] Test Example 1 A series of tests were conducted on Examples 1 to 5. Figure 2 The images show SEM images of M-GHP materials, where Fe-GHP and Co-GHP are clusters with no specific morphology, while Ni-GHP, Cu-GHP, and Zn-GHP are rod-shaped aggregates. Figure 3The images show the infrared spectra of phenyltetramine and the M-GHP material. Characteristic stretching vibrations of primary amines are observed in the phenyltetramine ligand between 3400-3450 cm⁻¹, but these vibrations disappear in M-GHP, indicating coordination between the amine functional group and the metal. Vibrational signals of the benzene ring skeleton between 1400-1650 cm⁻¹ are observed in both the phenyltetramine ligand and the M-GHP material, indicating that the benzene ring structure is fully preserved in M-GHP, confirming the successful preparation of the one-dimensional conjugated coordination polymer material. Figure 4 The X-ray diffraction patterns of the M-GHP materials are shown. Ni-GHP and Zn-GHP have strong crystallinity, Cu-GHP has weak crystallinity, and Fe-GHP and Co-GHP are amorphous.
[0055] Test Example 2 The elemental distribution of the Ni-GHP material prepared in Example 4 was tested. Figure 5 The results confirmed the presence and uniform distribution of C, N, and Ni elements in Ni-GHP.
[0056] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the claimed invention.
Claims
1. A method for the hydrogenation reduction of glycerol to 1,2-propanediol catalyzed by a glycerol hydrogenation catalyst, characterized in that, Includes the following steps: S1. Dissolve phenyltetramine tetrahydrochloride in deionized water and stir to obtain a homogeneous solution; S2. Dissolve the metal salt in deionized water and add it dropwise to the homogeneous solution obtained in S1; S3. Slowly add ammonia water to the S2 solution to adjust the pH to 8. Stir the reaction at room temperature. A dark precipitate will gradually form in the solution. S4. After the reaction is complete, the resulting mixture is filtered and the filter residue is washed several times with acetone, water and ethanol respectively. After drying, a one-dimensional conjugated coordination polymer material is obtained, denoted as M-GHP. S5. The M-GHP material obtained in S4 is pressed into tablets, ground and granulated, and then thoroughly mixed with quartz sand to obtain a quartz sand-supported M-GHP composite catalyst, denoted as M-GHP@SiO2. S6. The M-GHP@SiO2 composite catalyst material obtained in S5 is loaded into the reaction tube and carried out the catalytic hydrogenation reaction of glycerol in a fixed-bed reactor. S7. The obtained product is qualitatively and quantitatively detected by gas chromatography; The metal salt is selected from one of FeCl3, CoCl2·6H2O, CuSO4·5H2O, NiCl2·6H2O, and zinc acetate; The molar ratio of the phenyltetramine tetrahydrochloride to the metal salt is 1:1.1; The stirring reaction time for S3 at room temperature was 6 hours. In S5, after M-GHP granulation, 20-80 mesh particles are selected, and the quartz sand particles are 20-80 mesh. The S6 reaction was conducted at a temperature of 210-240℃, a pressure of 1.8-2 MPa, a glycerol mass fraction of 50%, and a hydrogen and nitrogen flow rate of 50 mL / min. -1 .
2. The method according to claim 1, characterized in that: In S1 and S2, the amount of phenyltetramine tetrahydrochloride is 1 mmol, the amount of metal salt is 1.1 mmol, and the amount of deionized water is 40 mL and 30 mL, respectively.
3. The method according to claim 1, characterized in that: The amount of M-GHP@SiO2 loaded in S6 is 10g.
Citation Information
Patent Citations
Supported M-X coordination polymer catalyst and preparation method and application thereof
CN107383382A